The Ideational Meaning of Text and Image Relation in Bahasa Inggris for Tenth Graders - Pahlevi, Sekar Ranis Anggita; Warsono, Warsono (English Education Journal, 2018)
The main objective of the study was to explain the realization of ideational meaning both in written text and visual image. Also to explain the realization of written text and visual image relations. This study was chosen because English textbook plays important roles in teaching EFL classroom, where the students’ understanding of texts in English textbook can be supported by images according to some studies on multimodality approach. This study was a qualitative study which the data were taken from English textbook entitled Bahasa Inggris published by the Ministry of Education and Culture. The data were gathered through observation sheet and analyzed using the teory of metalanguage and image-text relation. The result in the texts, however, material process has the highest percentage (60%) among the others.The findings also show that narrative processin the ideational meaning of image was higher use than conceptual process.The image-text relation analysis shows that most of the texts have elaborating relationship with the images because they gave detail information about text so this is could help the students to expand their critical thinking and strengthen their capacity in constructing and interpreting multimodal texts and also the benefit of this study is to improve teacher awareness of the importance of different making-meaning resources in the textbook.